(untitled) (Window of Public Health Journal, 2025)
Computer vision syndrome (CVS), also known as digital eye strain, is a group of eye diseases and vision-related problems that result from prolonged use of computers, tablets and mobile phone use. This study aims to determine the relationship between lighting intensity, work speed and sleep quality with Computer vision syndrome (CVS) among working computer users at PT. Japfa Comfeed Makassar. This type of research is a quantitative study using a Cross Sectional Study approach. The population of this study were 113 workers in the warehouse and finance & accounting departments. The sample of this study were 87 workers who were taken using the lambeshow method. Data analysis was carried out using univariate, bivariate and multivariate logistic regression tests to determine which variable had the strongest relationship to Computer vision syndrome (CVS) (α = 0.05). The results of this study showed that the P-value for age was 0.385, the P-value for gender was 0.116, the P-value for recent education was 0.967, the P-value for length of work was 0.338, the P-value for lighting intensity was 0.008, the P-value for work speed was 0.583 , P-value of sleep quality is 0.025. So it can be concluded that the most influential variable is the lighting intensity. The conclusion from this study is that the variables that have a relationship with Computer Vision Syndrome (CVS) are lighting intensity and sleep quality.